Enhancement algorithm for reverse loop technique on planar reverse loop antenna - Mohamad Harris Misran; Sharul Kamal Abdul Rahim; Maizatul Alice Meor Said; Mohd Azlishah Othman (Universitas Ahmad Dahlan, 2019)
Finding a trade-off balance between wireless transfer efficiency (WTE) and distance is a key issue in wireless energy transfer (WET). This paper presents a method of reducing the radical alteration in WTE versus distance, by using a reverse loop technique on planar reverse loop antenna (PRLA). The design focuses on 13.56 MHz Near Field Communication (NFC). The first stage uses mathematical modelling, based on an analytical approach, to determine the size of the reverse loop using Matlab. The proposed model predicts the size of the reverse loop to stabilize the WTE at a closer distance. Next, full-wave electromagnetic simulations are applied, using the computer simulation technology (CST) MICROWAVE STUDIO®, to determine the WTE effect with distance changes with mismatch condition. Planar loop antennas (PLAs) are fabricated on glass-reinforced epoxy laminated sheets (FR4). A validation of the simulation result in a real test scenario, using these PLAs and PRLA, confirms a stability enhancement in WTE at closer distance using the reverse loop technique, compared to conventional designs.